The allure of machinic life : cybernetics, artificial life, and the new AI. - Johnston, John (Cambridge : MIT press, 2008)
From cybernetics to machinic philosophy -- Cybernetics and the new complexity of machines -- The in-mixing of machines: cybernetics and psychoanalysis -- Machinic philosophy: assemblages, information, chaotic flow -- Machinic life -- Vital cells: cellular automata, artificial life, autopoiesis -- Digital evolution and the emergence of complexity -- Machinic intelligence -- The decoded couple: artificial intelligence and cognitive science -- The new Al: behavior-based robotics, autonomous agents, and artificial evolution -- Learning from neuroscience: new prospects for building intelligent machines.
boek